2018
DOI: 10.1016/j.ygyno.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel sequencing analysis of mucinous ovarian carcinomas: genomic profiling and differential diagnoses

Abstract: Our findings suggest that the assessment of mutations affecting TP53, KRAS, PIK3CA, ARID1A and POLE, and DNA MMR protein expression may be used to further aid the diagnosis and treatment decision-making of primary MOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…It was reported that 79.0% of MC and 0.6% of HGSC have KRAS mutation. 25 Recently, KRAS mutation was found in 42% of EC. 24 Although KRAS is the most frequently mutated oncogene in human cancers, no therapeutic agent directly targeting RAS has yet been approved.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 79.0% of MC and 0.6% of HGSC have KRAS mutation. 25 Recently, KRAS mutation was found in 42% of EC. 24 Although KRAS is the most frequently mutated oncogene in human cancers, no therapeutic agent directly targeting RAS has yet been approved.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of our primary mucinous ovarian cancer cohort with other mucin-producing malignancies identified significant differences in the mutational profiles of all histologies except that of mucinous pancreatic carcinoma. Our previous study also highlighted the clinical value of using molecular profiling to diagnose primary mucinous ovarian cancer and identify potentially targetable mutations and copy number alterations 17. A recently published paper by Meagher et al advocates for molecular profiling of mucinous ovarian cancer of uncertain primary origin.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, it has been reported that lack of Cdkn2a in V600E BRAF mutated melanocytes in rodents is associated with rare progression to melanoma [40]. In MOC, Cdkn2a/b homozygous deletions/mutations were detected at high frequencies [41]. From these reports, it appears that loss of Cdkn2a in mucinous ovarian tumors with V600E BRAF mutation impairs progression to carcinoma.…”
Section: Discussionmentioning
confidence: 99%